Inuit family in snow house, Cape Fullerton or Repulse Bay, Canadian Arctic - Comer, George (Creator) (Ownership Statement: Mystic Seaport, 1907)
Four Inuit, including one child, sit inside what appears to be a snow house at Cape Fullerton or Repulse Bay, Canadian Arctic. The group is identified as """"A man with his two wives in Igloo or snow house."""" Lifestyle Livelihood Infrastructure Title supplied by cataloger. Same group as depicted in 1983.25.34. Taken by Captain George Comer (1858-1937), a sealer and whaling captain from East Haddam. He went to sea while still in his teens and was later master of vessels from both New London and New Bedford. Comer participated in voyages involved in polar expeditions and was noted for his studies of Arctic peoples and their environment.